Construção e circulação das gramáticas de Língua Portuguesa no Brasil no século XIX: o Tratado de Língua Vernácula de Brício Cardoso - Gally, Christianne de Menezes (2013)
Considering grammar as a cultural object object built by man for socially and culturally constructed this investigation, after proposing criteria for analysis, from the point of view of the new Cultural history (or history of linguistic ideas), uses the concepts of ownership and representation, whose goal is to understand, through the Tratado da Língua Vernácula, written by Brício Cardoso, the relations established between the text, the object which supports specific practices that produced conceptual and cultural settings and entered in his time. With this analysis, It is intended to assert that the grammars produced are all important cultural artifacts of their time and, because of that, historical source that presents evidence of unique experiences. In other words, a grammar is built with a specific goal to meet a specific public, required for a particular school, almost always written by eminent teachers in their social environment that if other apropriavam selected models as their cultural baggage, your mental utensilagem